Addition of gourami (Osphronemus goramy) fish scale powder on porosity of glass ionomer cement - Erawati Wulandari; Farah Rachmah Aulia Wardani; Nadie Fatimattuzahro; I Dewa Ayu Ratna Dewanti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Porosity is one of the disadvantages of glass ionomer cement (GIC) restorative materials, as it causes a reduction in strength and durability; the greater the porosity, the lower the strength of the restorative material and vice versa. As gourami fish scales contain calcium and phosphate, they have the potential to reduce the porosity of GIC. Purpose: This study aimed to analyse the effect of adding gourami fish scale powder (GFSP) on the pore size and porosity level of the GIC. Methods: This experimental research included a post-test-only control. The GFSP was fabricated using the freeze-drying method. Sixteen Fuji IX Extra sample cylinders with a diameter of 5 mm and a height of 3 mm were divided into four groups: K0, which comprised GIC without the addition of GFSP; K1, which contained GIC powder + 2.5% GFSP (by weight); K2, which comprised GIC powder + 5% GFSP (by weight), and K3, which contained GIC powder + 10% GFSP (by weight). The samples were observed using scanning electron microscopy and measured using ImageJ software. Data were analysed using a one-way analysis of variance (ANOVA) test. Results: The addition of 2.5% GFSP (by weight) produced the smallest pore size and lowest porosity, while the one-way ANOVA test results were significant among all groups at p = 0.000. There was no significant difference in pore sizes between K0 and K1 (p = 0.359), but a significant difference was found in the level of porosity (p = 0.024). Conclusion: The addition of GFSP affected the porosity of the GIC; the pore size and porosity level of the GIC were reduced by the addition of 2.5% GFSP.